Innovators' Marketplace Using Games to Activate and Train Innovators - Ohsawa, Yukio; Nishihara, Yoko.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book presents a powerful method for innovation that reinforces combinatorial and analogical thoughts, with interdisciplinary communications among stakeholders in the market. In this method called Innovators' Marketplace, two games - Innovators' Market Game and Analogy Game - accelerate the spiral of innovation with visualizing data on the connectivity of pieces of existing knowledge. Some players invent ideas by connecting and combining pre-existing knowledge, while others evaluate the ideas to decide whether or not to buy. In a joyful atmosphere created by the games, players look beyond resistance to criticism, as experiments real cases show. They will start thinking and talking about the best segment of the majority, latent requirements in the future market, and scenarios for satisfying those requirements. This process embodies the principle that an interdisciplinary combination of business actors and resources, possibly with the appearance of new actors, triggers innovation.
1. Introduction: innovation as a serious entertainment -- 2. Chance discovery as value sensing for innovation -- 3. Using maps for scenario externalization -- 4. Theories for innovative thought and communication -- 5. Analogy game: training and activating analogical thought -- 6. Innovators$1 (Bmarket game: communication with and for innovative thinking -- 7. Evidence-based guidelines for innovators$1 (Bmarketplace -- 8. Innovators$1 (Bmarketplace as integrated process: an industrial case -- 9. Application case: policies for long-lasting safety of nuclear power plants -- 10. Img on the web? And conclusion -- Index.s
Keywords: Business; Organization; Planning; Management; Industrial management; Business and Management; Innovation/Technology Management; Organization; Electronic books